To solve for y, you need to isolate/get the variable "y" by itself in the equation:
a(n + y) = 10y + 32 First distribute a into (n + y)
(a)n + (a)y = 10y + 32
an + ay = 10y + 32 Subtract an on both sides
an - an + ay = 10y + 32 - an
ay = 10y + 32 - an Subtract 10y on both sides to get "y" on one side of the equation
ay - 10y = 10y - 10y + 32 - an
ay - 10y = 32 - an Now take out the y in (ay - 10y)
y(a - 10) = 32 - an Divide (a - 10) on both sides to get "y" by itself
![(y(a-10))/((a-10)) =(32-an)/((a-10))](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jqwexx47yfqn4p4vz6x9ydmjpcrcwnocbn.png)
![y=(32-an)/(a-10)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5d5xvzdphsj8whzn1flx5rtuegy8kfosju.png)